Students Perspectives Toward Autonomy learning Through Jigsaw Method in Semantics and Pragmatics Subject, Hasanuddin - Tri Utami Rahardjo; Hasanuddin NA; Rasuna R Thalib (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2019)
This study is aimed to explore the students’ perspectives toward Autonomy learning by implementing Jigsaw method in Semantics and Pragmatics subject. This study intended to answer the following question: what are the students’ perspectives toward autonomy learning through jigsaw method in semantics and pragmatics subject? Qualitative method has been selected as the methodology of this study and used interview as the tool of gathering the data. This study involved ten participants in class A of 2015 students at English Department. Consequently, interview question developed by the researcher and the result were analyzed and divided based on two indicators of perspective from Robbin (2003, p.124-130) cited in Wulandari (2012, p.11), including; acceptance/ absorption and evaluation. The result of this study revealed that the students agree about using the Jigsaw method in Semantics and Pragmatics subject, which is important in teaching and learning activity. They mentioned that they are really interested of the implementation of autonomy learning through jigsaw method gave many positive impacts such as make students independent and helps students’ having responsibility for their learning. Besides, the students found the difficulties about the material in semantics and pragmatics; it is not become a big problem because Jigsaw method is the way to resolve. It aids lecturer in order to help the students to get more explanation. Therefore, the lecturer’s position is also very important in the learning process. This study recommends the lecturer to implement the Jigsaw method in order to enhance students autonomous in learning subjects.